Caracterização da produção e avaliação de indicadores de qualidade tecnológica de amostras de melado do estado de São Paulo - Silva, Mariane Martins Pereira da (Universidade Federal de São Carlos, 2012)
The molasses, a syrup made from the juice of sugarcane juice, is a sweet liquid, nutritious, homemade and very popular in the Northeast Region of Brazil. It is few explored by small farmers in São Paulo State and, because this, the present study aimed to identify how is the professional involved in its production at São Paulo State through a questionnaire. Whit the returns obtained from the questionnaires and the results of physicochemical analyzes, it can be concluded that few producers know the best way to produce molasses. It s necessary instruction and training for these to be able to exploit this market share.
Characterization of production and evaluation of technological quality indicators of molasses samples from São Paulo state
Keywords: Cana-de-açúcar; Melado; Cana-de-açúcar derivados; Qualidade; Caracterização; Avaliação; Molasse; Quality; CIENCIAS AGRARIAS